Injectable hydrogels based on MPEG-PCL-RGD and BMSCs for bone tissue engineering - Kim, Hyun Joo; You, Su Jung; Yang, Dae Hyeok; Eun, Jin; Park, Hae Kwan; Kim, Moon Suk; Chun, Heung Jae (Biomaterials Science, 2020)
The aim of this study was to investigate the osteogenic potential of bone marrow-derived mesenchymal stem cells (BMSCs) seeded on novel thermosensitive in situ forming hydrogel systems comprising methoxy polyethylene glycol-polycaprolactone (MP) and RGD-conjugated MP (MP-RGD) in vitro and in vivo. Real-time polymerase chain reaction (PCR) together with immunofluorescence staining revealed the strong expression of osteogenic markers (collagen 1 and osteocalcin) of BMSCs in MP/MP-RGD samples compared to MP samples. PCR array testing also showed the upregulation of the interconnected signaling networks regulating cell proliferation and differentiation, which was further verified through the Kyoto Encyclopedia of Genes and Genomes pathway analysis. Histological findings and computed tomographic analysis demonstrated that the MP/MP-RGD hydrogel dramatically promoted new bone formation in a rabbit calvarial defect model. In conclusion, this hydrogel appears to elicit cellular behaviors desired for bone tissue regeneration. This journal is
Keywords: Bone marrow-derived mesenchymal stem cells; Bone tissue engineering; Bone tissue regeneration; Computed tomographic; Immunofluorescence staining; Injectable hydrogels; Methoxypolyethylene glycol; Real time polymerase chain reactions; Animals; Cell Differentiation; Cell Proliferation; Cells, Cultured; Hydrogels; Oligopeptides; Osteogenesis; Polyesters; Polyethylene Glycols; Rabbits; Tissue Engineering